Double-edged functions of hemopexin in hematological related diseases: from basic mechanisms to clinical application - Li, Yijin; Chen, Renyu; Wang, Chaofan; Deng, Jun; Luo, Shanshan (Frontiers in Immunology, 2023)
It is now understood that hemolysis and the subsequent release of heme into circulation play a critical role in driving the progression of various diseases. Hemopexin (HPX), a heme-binding protein with the highest affinity for heme in plasma, serves as an effective antagonist against heme toxicity resulting from severe acute or chronic hemolysis. In the present study, changes in HPX concentration were characterized at different stages of hemolytic diseases, underscoring its potential as a biomarker for assessing disease progression and prognosis. In many heme overload-driven conditions, such as sickle cell disease, transfusion-induced hemolysis, and sepsis, endogenous HPX levels are often insufficient to provide protection. Consequently, there is growing interest in developing HPX therapeutics to mitigate toxic heme exposure. Strategies include HPX supplementation when endogenous levels are depleted and enhancing HPX’s functionality through modifications, offering a potent defense against heme toxicity. It is worth noting that HPX may also exert deleterious effects under certain circumstances. This review aims to provide a comprehensive overview of HPX’s roles in the progression and prognosis of hematological diseases. It highlights HPX-based clinical therapies for different hematological disorders, discusses advancements in HPX production and modification technologies, and offers a theoretical basis for the clinical application of HPX.